Effect of polyphenols from Vicia faba L on lipase activity and melanogenesis*. Issue 16 (18th August 2018) - Allam, Ahmed E.; Nafady, Alaa M.; Nakagawa, Toshinori; Takemoto, Naomichi; Shimizu, Kuniyoshi
Abstract: Two new flavonoid glycosides, kaempferol 3- O - α -L-rhamnopyranosyl (1→6) (3′′-acetyl)- β -D-galactopyranoside1 and kaempferol 3- O - α -L-arabinopyranosyl-5- O - α -L-rhamnopyranoside2, along with six known ones3–8 were isolated from the flowers of Vicia faba L. (Fabaceae). Methanol extract and the isolated compounds were tested against lipase and melanogenesis inhibition activities and resulted in that compound2 showed 53 and 77% lipase inhibition activity in concentrations of 400 and 800 μg/mL, respectively. For melanogenesis, compounds2, 3 and4 exhibited potent melanogenesis inhibition activity where the melanin content in melanoma cells was decreased to be about 57.5, 56 and 61%, respectively, with no obvious melanocytotoxicity. The rest of compounds showed weak to moderate activity. The results of melanogenesis inhibition activity of this study suggested the potential use of Vicia faba flowers as a skin-whitening agent and reveal the flowers to be a rich source of important phytochemicals with antilipase and melanogenesis inhibitory activity. Abstract :